O Team Manager na gestão operacional de uma equipa de futebol da Futebol Clube do Porto - Futebol, SAD - José Miguel Marques dos Santos (2019)
The preparation of this internship report, which is one of the necessary components to complete the Master's Degree in Sports Management at the Faculty of Sports of the University of Porto, served to present and frame the professional internship that I did at FCP - Futebol, SAD during the 2018 / 2019 season. During this time I was Team Manager in the football teams of the mentioned club, with closer proximity to the under 7 and under 8 squads, but also with participation, usually at competitive times, in the teams until the under 14. After a conceptual framework on the issues related to professional practice, a description is made of the entity in which I performed it, covering the FCP Group as a whole and not just the FCP - Futebol, SAD, to which, of course, more emphasis is placed. Subsequently, all the activities I performed during the internship are detailed, including from pre-season to those performed during various competitive times and those performed during the week. Besides that, in the form of a scientific paper, it is presented my systematic review about the tasks and competencies of sports managers, as well as a description of the work initiated about the FCP - Futebol, SAD team manager profile. Finally, some skills I have acquired and improved, such as communicative and decision-making skills, human resource management, as well as coping with pressure, are listed. Tournaments were the moments that most contributed to this evolution, which in turn facilitated my entrance in the job market.